Dietary α-ketoglutarate alleviates glycinin and β-conglycinin induced damage in the intestine of mirror carp (Cyprinus carpio) - Luo, Qiaohua; Qian, Rendong; Qiu, Zongsheng; Yamamoto, Fernando Y.; Du, Yingying; Lin, Xiaowen; Zhao, Jianhua; Xu, Qiyou (Frontiers in Immunology, 2023)
This study investigated the glycinin and β-conglycinin induced intestinal damage and α-ketoglutarate alleviating the damage of glycinin and β-conglycinin in intestinal. Carp were randomly divided into six dietary groups: containing fish meal (FM) as the protein source, soybean meal (SM), glycinin (FMG), β-conglycinin (FMc), glycinin+1.0% α-ketoglutarate (AKG) (FMGA), β-conglycinin+1.0% AKG (FMcA). The intestines were collected on 7th, and the hepatopancreas and intestines were collected on 56th. Fish treated with SM and FMc displayed reduced weight gain, specific growth rate, and protein efficiency. On 56th day, Fish fed on SM, FMG and FMc presented lower superoxide dismutase (SOD) activities. FMGA and FMcA had higher SOD activity than those fed on the FMG and FMc, respectively. In intestine, fish fed on the SM diets collected on 7th presented upregulated the expression of transforming growth factor beta (TGFβ1), AMP-activated protein kinase beta (AMPKβ), AMPKγ, and acetyl-CoA carboxylase (ACC). Fish fed FMG presented upregulated expression of tumor necrosis factor alpha (TNF-α), TGFβ1, caspase9, and AMPKγ, while downregulated the expression of claudin7 and AMPKα. FMc group presented upregulated expression of TGFβ1, caspase3, caspase8, and ACC. Fish fed FMGA showed upregulated expression of TGFβ1, claudin3c, claudin7, while downregulating the expression of TNF-α and AMPKγ when compared to fish fed FMG diet. FMcA upregulated the expression of TGFβ1, claudin3c than fed on the FMc. In intestine, the villus height and mucosal thickness of the proximal intestine (PI) and the distal intestine (DI) were decreased and crypt depth of the PI and mid intestine (MI) were increased in SM, FMG and FMc. In addition, fish fed on SM, FMG and FMc presented lower citrate synthase (CS), isocitrate dehydrogenase (ICD), α-ketoglutarate dehydrogenase complex (α-KGDHC) Na+/K+-ATPase activity in DI. FMGA had higher CS, ICD, α-KGDHC, and Na+/K+-ATPase activity in PI and MI than those fed on the FMG. FMcA had higher Na+/K+-ATPase activity in MI. In conclusion, dietary soybean meal destroys the intestine’s health, the adverse effects are related to the presence of β-conglycinin and glycinin, especially glycinin. AKG may regulate intestinal energy via tricarboxylic acid cycle, thereby alleviating the damage intestinal morphology caused by the dietary soybean antigen proteins.